Development of new CdZnTe detectors for room‐temperature high‐flux radiation measurements. (1st February 2017) - Abbene, Leonardo; Gerardi, Gaetano; Raso, Giuseppe; Principato, Fabio; Zambelli, Nicola; Benassi, Giacomo; Bettelli, Manuele; Zappettini, Andrea
Abstract : The performances of new travelling‐heater‐method‐grown CZT detectors, recently developed at IMEM‐CNR (Parma, Italy), are presented. The detectors, characterized by low leakage currents at room temperature (4.7 nA cm −2 at 1000 V cm −1 ), allow good room‐temperature operation even at high bias voltages (>7000 V cm −1 ). Abstract : Recently, CdZnTe (CZT) detectors have been widely proposed and developed for room‐temperature X‐ray spectroscopy even at high fluxes, and great efforts have been made on both the device and the crystal growth technologies. In this work, the performance of new travelling‐heater‐method (THM)‐grown CZT detectors, recently developed at IMEM‐CNR Parma, Italy, is presented. Thick planar detectors (3 mm thick) with gold electroless contacts were realised, with a planar cathode covering the detector surface (4.1 mm × 4.1 mm) and a central anode (2 mm × 2 mm) surrounded by a guard‐ring electrode. The detectors, characterized by low leakage currents at room temperature (4.7 nA cm −2 at 1000 V cm −1 ), allow good room‐temperature operation even at high bias voltages (>7000 V cm −1 ). At low rates (200 counts s −1 ), the detectors exhibit an energy resolution around 4% FWHM at 59.5 keV ( 241 Am source) up to 2200 V, by using commercial front‐end electronics (A250F/NF charge‐sensitive preamplifier, Amptek, USA; nominal equivalent noise charge of 100 electrons RMS). At high rates (1 Mcounts s −1 ), the detectors, coupled to a custom‐designed digital pulse processing electronics developed at DiFC of University of Palermo (Italy), show low spectroscopic degradations: energy resolution values of 8% and 9.7% FWHM at 59.5 keV ( 241 Am source) were measured, with throughputs of 0.4% and 60% at 1 Mcounts s −1, respectively. An energy resolution of 7.7% FWHM at 122.1 keV ( 57 Co source) with a throughput of 50% was obtained at 550 kcounts s −1 (energy resolution of 3.2% at low rate). These activities are in the framework of an Italian research project on the development of energy‐resolved photon‐counting systems for high‐flux energy‐resolved X‐ray imaging.